European Strategic Autonomy and Small States' Security In the Shadow of Power - Česnakas, Giedrius; Juozaitis, Justinas (Routledge Studies in European Security and Strategy, 2023)
This book analyses whether the EU's drift towards European strategic autonomy presents a challenge or a window of opportunity for its small member states to advance their security interests. The volume presents small states' perceptions of European strategic autonomy, highlighting their expectations and concerns. The chapters focus on the depth and breadth of European strategic autonomy, national security considerations, assessment of the impact on transatlantic relations, the expected outputs, and its potential impact on the EU's institutional structure. It also shows how systemic circumstances and the interests of powerful states, either belonging to the EU (France, Germany, and Poland) or having a significant say in European security architecture (the US), establish opportunities and constraints for the small states to shape European strategic autonomy. In particular, the study focuses on the diverging interests of the Baltic states (Estonia, Latvia, and Lithuania), Belgium, Denmark, Greece, Hungary, and the Netherlands. It demonstrates that, in most cases, European strategic autonomy is perceived not as an alternative to NATO but as a supplementary element that could facilitate the development of national military capabilities, indigenous defence industries and resilience to non-military threats. Ultimately, the book suggests that national approaches towards European strategic autonomy mainly stem from pragmatic national security and foreign policy considerations, while largely ignoring grand strategic ideas. This book will be of much interest to students of European politics, security studies, and international relations. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.